The Practice of Pokdarwis Involvement and The Application of Design Activism in Developing Decorative Bambu Products - Atik Prihatiningrum; Diyas Widiyarti; Eka Vuspa Sari (International Journal of Community Service Learning, 2026)
The limited knowledge and skills of the Tourism Awareness Group (Pokdarwis) in producing a variety of decorative bamboo products, the suboptimal quality of promotional content on social media, and the lack of distinctiveness that reflects local identity are the main problems in developing bamboo products. These conditions affect the low competitiveness of the products and the weak branding of the cultural destinations managed by Pokdarwis Arga Tirta. This community service activity aims to increase the capacity of knowledge and skills of Pokdarwis Arga Tirta in developing decorative bamboo products through the application of a design activism approach and participatory Pokdarwis involvement practices. This community service uses a qualitative-participatory approach. The service subjects were 20 Pokdarwis from Arga Tirta. Data collection methods included observation, interviews, documentation, and pre- and post-tests to measure knowledge gains, using instruments such as observation sheets, interview guides, and written tests. The data analysis method used a simple qualitative and quantitative descriptive analysis. The service results showed an increase in partner capacity of 78% by producing 9 product variations and 7 variations of decorative bamboo motifs based on local wisdom. In conclusion, design activism-based training and mentoring were effective in enhancing the understanding, practical skills, and independence of the Arga Tirta Tourism Group (Pokdarwis) in producing local creative products that support sustainable cultural destination branding.